Reformulasi Undang-Undang Pilkada: Upaya Penanganan Praktik Money Politic di Indonesia - Insan Tajali Nur; Vijae Yehezkiel Simanjuntak (CV Putra Publisher, 2024)
The Head Election is one of the democratic parties of the Indonesian people. Pilkada is a form of leader regeneration in order to create new ideas and thoughts in an area. Through regional elections, it is hoped that qualified regional leaders will be elected who are in accordance with the will of the people. The practice of holding regional elections in Indonesia has reaped problems which have resulted in the violation of democratic principles. The problem that continues to occur is the practice of money politics which aims to influence the hearts of voters when conducting elections. This problem is caused by various sectors, one of which is regulation. The regulation of money politics, which each tries to divide the provisions of its legal subject, and the existence of structured, systematic and massive (TSM) elements in the administration of administrative sanctions are things that hinder the handling of money politics in Indonesia. Thus, this research will examine the reformulation needed to be able to deal with money politics. The research method used is a normative method. The research results show that there is an urgency to change the regional election law, especially regarding the subject of money politics and the requirements for the TSM element in granting administrative sanctions